wyznacz V(x) *W(x) gdy V(x) =(1-2x)^3, natomiast W(x)= ( pierw. z 2 - x) * (pierw. z 2 + x)
V(x)=(1-2x)³=1-6x+12x²-8x³
W(x)=(√2-x)(√2+x)=2-x²
V(x)W(x)=(1-6x+12x²-8x³)(2-x²)=2-x²-12x+6x³+24x²-12x⁴-16x³+8x⁵=
=8x⁵-12x⁴-10x³+23x²-12x+2
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
V(x)=(1-2x)³=1-6x+12x²-8x³
W(x)=(√2-x)(√2+x)=2-x²
V(x)W(x)=(1-6x+12x²-8x³)(2-x²)=2-x²-12x+6x³+24x²-12x⁴-16x³+8x⁵=
=8x⁵-12x⁴-10x³+23x²-12x+2